Only mr. darcy will do ebook - Louise, Kara (2011)
Her worst fears come true... After her father's death, Elizabeth Bennet goes to work as a governess. Little does she know the Willstones are social acquaintances of the Bingleys and the Darcys, and Elizabeth finds herself once again drawn into Mr. Darcy's orbit. To make matters worse, Mrs. Willstone's sister sets her sights on Mr. Darcy. With Elizabeth's social status even lower than it was before, she knows she must abandon all hope of Darcy renewing his proposals, even as she begins to see him in a completely different light... Praise for Darcy's Voyage "Refreshing... a tale of romance, intrigue, and adventure...that made me sigh in all the right places and laugh out loud at the most surprising moments." —Austenprose